Tailoring flux composition to control welding fume and hexavalent chromium emissions in flux cored arc welding - Sungyo Jung; Gi Taek Oh; Seungjin Jung; Chungsik Yoon (Journal of Advanced Joining Processes)
Flux-cored arc welding (FCAW) generates hazardous byproducts such as welding fumes and hexavalent chromium (Cr(VI)), posing significant health and environmental risks. This study investigated the effectiveness of modifying specific flux components in flux-cored wires (FCWs) to reduce these emissions. One base FCW and ten flux-modified FCWs were tested under controlled conditions, capturing emissions for gravimetric and Cr(VI) analysis. Flux compositions were determined using X-ray fluorescence. Statistical analyses, including difference tests, correlation, and multiple linear regression, were conducted to evaluate the association between the content of flux components and emission rates. Sodium (Na) content in the flux was positively associated with increased emission of welding fumes and Cr(VI), while titanium (Ti) content showed a negative association. Increasing the contents of fluorine (F), potassium (K), and chromium (Cr) in the flux raised welding fume emission but reduced Cr(VI) emissions. Strategic adjustments in flux composition, specifically increasing Ti, silicon (Si) and zirconium (Zr) while decreasing Cr, K, Na, and F content, significantly reduced welding fume emissions by up to 32.4 % and Cr(VI) emissions by 95.4 %. These findings suggest that tailoring flux composition can effectively mitigate occupational and environmental hazards, enhance welder safety, and promote more sustainable FCAW practices without compromising welding performance.